Analisis Saluran Pemasaran Serundeng Sapi (Studi Kasus pada Agroindustri Serundeng Sapi Liyan di Kelurahan Kotabaru Kecamatan Cibeureum Kota Tasikmalaya) - Sujaya, Dedi Herdiansah; Pardani, Cecep (Universitas Galuh, 2025)
This research aims to determine: (1) The marketing channels for beef serundeng in the Liyan cattle serundeng Agroindustry, (2) The amount of margin, costs and profits of marketing beef serundeng in the Liyan cattle serundeng Agroindustry, (3) The size of the price share received by producers (producer's share) cow serundeng in the Liyan cow serundeng Agroindustry from retail prices. The research method used is a case study. The data obtained consisted of primary and secondary data. The number of respondents in this study was four people, consisting of one manufacturer and three retailers. The research results show that: (1) There are two marketing channels, that was Marketing channels 1: Producer à Consumer, and Marketing Channels 2: Producer à Traders Retailers à Consumers. (2) In channel 1 there are no margins, profits and marketing costs, because consumers come directly to buy from producers. Meanwhile, in channel 2 the marketing margin is IDR. 5,000,- per piece with marketing costs of Rp. 1,000,- per pc so that the marketing profit is IDR. 4,000,- per pc. (3) The share of the price received by producers (Producer's Share) in marketing channel 1 is 100 percent, and in marketing channel 2 is 75 percent.